P22 protein complex in the serodiagnosis of animal tuberculosis: Antigenic stability and cross-reactivity with Corynebacterium pseudotuberculosis infection. (November 2022) - Barral, Thiago Doria; Infantes-Lorenzo, José A.; Moreno, Inmaculada; de Garnica García, M. Gracia; de Val, Bernat Pérez; Gortázar, Christian; Meyer, Roberto; Portela, Ricardo D.; Domínguez, Lucas; Domínguez, Mercedes; Balseiro, Ana
Abstract: The P22 ELISA was recently developed for the serodiagnosis of animal tuberculosis. Herein, the stability of the P22 antigen in different presentations and storage conditions, and the cross-reactivity with Corynebacterium pseudotuberculosis infection in small ruminants were evaluated. For the stability assay, serum samples from cows, sheep, goats, alpacas, badgers, and wild boar were used in the P22 ELISA. The cross-reactivity analysis used sera from sheep and goats with caseous lymphadenitis (CLA). Differences in the immune recognition of P22 were found when the antigen was stored at 40 °C, but without altering the negative or positive status of each sample. P22 ELISA presented 5.71 % cross-reactivity when CLA-positive sheep were evaluated, but no cross-reaction was observed among CLA-positive goat serum samples. This study showed that the P22 protein complex is stable under different formulations and temperatures, and that the assay presents a low cross-reactivity with CLA. Highlights: P22 ELISA is a very stable diagnostic tool for tuberculosis diagnosis. P22 protein complex is more stable when maintained in solution at 4 °C. Freeze-drying is a reliable tool for P22 storage. P22 ELISA did not present cross-reactions for CLA-positive goats. P22 ELISA presented a 5.7 % cross-reactivity for CLA-positive sheep.